L’Appétit Sauvage: The Blissful Utopia of Desire and Excess in Ben Jonson’s Bartholomew Fair - Rato, Rui (Cadernos de Literatura Comparada, 2017)
In Ben Jonson’s Bartholomew Fair we find a realm of apparent freedom and levity, wherein the characters feel indulged to express themselves with far greater poignancy than it would happen in the regular world of law and order. The suspension of societal authority and structure brought about by this most voluptuous carnival leads to a dynamic flow of desire and want that normally would be restrained by good sense and justice, but as we find plainly in the play Justice is like a fish out of water amidst the ebullient effervescence of the appetites which define the Fair. Free to pursue their most sincere needs, pending toward extravagance as all desire which is taken to excess is wont to do, the characters quickly find themselves at home in this most savage of places, where there is nourishment to sate all palates, even the most depraved ones. But as even scoundrels dream of a better world, it may just be that Bartholomew Fair is that very world; where knaves and fools dance interminably in a merry-go-round, and where the impetus of Nature is uninhibited by unsophisticated reason. Does the utopian impulse, which I argue can be found within the play, come with this awareness of a need to binge and purge in a place which is accommodating to all kinds, and if so how does the appetite of the characters determine their utopian identity in accordance with the principle of nature found in need? To explore the nature of the Fair and the appetite which defines it, I will discuss primarily George Bataille’s principle of general economy and sovereignty announced in The Accursed Share and Jacques Derrida’s understanding of sovereignty in “From Restricted to General Economy: A Hegelianism Without Reserve”. It can certainly be that the extraordinary impulse of consumption and excess which appears in the play can be discussed within the bounds of Utopian imagination, gifting disorder with the laurels it much deserves, earned by the eager provision of essential perspective on an otherwise flat reality, restriction being far too often the key to a Dystopia.